Adaptive Governance Frameworks for Disaster Risk Reduction in Coastal Ternate - Kyren Kyren (Pemuda Peduli Publikasi Insan Ilmiah, 2024)
Purpose: This take a look at examines the position of adaptive governance frameworks in catastrophe chance reduction efforts in coastal Ternate and the village of Pangkalan Jati in Sumatra, Indonesia. Subjects and Methods: Through a combined-methods technique integrating qualitative interviews and quantitative surveys, the study explores the effectiveness of governance systems and their effect on network resilience. Descriptive records reveal demographic characteristics, perceptions of governance effectiveness, and stages of catastrophe preparedness among individuals. Inferential analyses, which includes paired-samples t-checks, regression analyses, ANCOVA, and Pearson correlational analyses, elucidate the relationships between governance effectiveness, socio-economic elements, and disaster preparedness rankings. Results: The findings underscore the significance of transparency, network engagement, adaptability, income, and education level in selling catastrophe resilience. Conclusions: Ultimately, implementing adaptive governance frameworks that foster collaboration and inclusivity is essential for mitigating catastrophe risks and building sustainable groups in coastal regions.